Management Dialectical Tension di Desa Pancasila, Kecamatan Turi, Lamongan dalam Meminimalkan Ketegangan pada Keluarga - Brigitta Revia Sandy Fista; Akhsaniyah Akhsaniyah (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2021)
This study focuses on the dialectical tension management strategy for married couples of different religions in Pancasila Village, Turi District, Balun, Lamongan. Balun Village was chosen because it has a high level of religious tolerance. Using the Rational Dialectical theoretical perspective, this study reveals how individuals feel in communicating, identifies the causes of tension in communication, and communication strategies in overcoming tensions in interfaith families. This study uses a qualitative-descriptive approach with a case study method, intending to be able to describe in detail how the tensions formed in interfaith families in Balun Village are minimized. Data collection techniques were carried out by in-depth interviews and observations, to obtain a complete picture of their daily communication practices. The results of this study indicate that there are different dialectical tension management patterns, which are based on the level of tension that arises and the issues that trigger tension. The main cause of tension in interfaith family communication is related to two things; lack of openness of the parties and the influence of stereotypes on different ethnicities in the family.